Pengaruh Pengalaman Kerja, Independensi,Obyektifitas, Integritas, Dan KompetensiTerhadap Kualitas Hasil Audit(Studi Empiris Pada Auditor Inspektorat Daerah Kota Surakarta, Kabupaten Karanganyar, dan Kabupaten Boyolali) - Widiastuti, Wiwid; , Eny Kusumawati.,SE.,MM.,AK,CA (2016)
This study aims to determine empirically on the influence of work experience,independence, objectivity, integrity and competence of the quality of the audit results on the Regional Inspectorate Auditor in Surakarta, Karanganyar regency and Boyolali. This research is quantitative, The data used in this study are primary and methods of data collection in this study using a questionnaire. The population in this study were all auditors working in the Inspectorate Surakarta, Karanganyar regency and Boyolali. The sample in this study was 63 auditors.Where the sampling technique used purposive sampling with criteria auditor who has worked for at least 1 year. The statistical method used to test the hypothesis is multiple linear regression analysis. Based on the research found that the variable work experience, objectivity, and integrity have a significant influence on the quality of the audit results, while variable influential independence and competence are not on the quality of the audit results. Keywords: Work Experience, Independence, Objectivity, Integrity, Competence, Work Experience, Independence, Objectivity, Integrity and Competence.